Burden of Care among Mothers Having Children with Down Syndrome - Mishra, Tulashi Adhikari; Pandey , Kabita; Bhujel , Bishnu; Adhikari , Shova (Journal of Nepal Health Research Council, 2023)
Background: Down syndrome is the most common chromosomal disorder associated with mental retardation. Parents who are the primary caregivers of a child with a disability face numerous challenges in their day-to-day life. The objective of the study was to find out the burden of care among mothers having children with down syndrome. Methods: A descriptive cross-sectional study was carried out among 96 mothers having down syndrome children enrolled in the Down Syndrome Society, Nepal. Purposive Sampling technique was adopted for data collection. The Modified Caregiver Strain Index tool was used to collect data through interview. Data were collected from June 14, 2021 to August 1, 2021, which was analyzed by using descriptive and inferential statistics. Results: Findings revealed that majority of the mothers (77.1%) had high level of burden of care. Majority (89.6%) of the mothers involved in the study were always overwhelmed about their child’s conditions. More than half (55.2%) of the mothers were always financially strained in care giving, 57.3% had always done work adjustments and 60.4% of mothers always had emotional adjustments to be made. Similarly, 53.1% participants always felt that care giving was a physical strain. Burden of care was significantly associated with the age of delivery (p value= 0.008). Conclusions: The study concludes that mothers having children with down syndrome tend to have high level of burden of care and it is associated with the age at delivery. Therefore, health care providers including concerned authority are recommended to conduct different programs to support the caregivers in order to reduce their burden as well as to raise awareness program related to preventive measures of down syndrome in community. Keywords: Burden of care; down syndrome; mothers